Overcoming barriers to NHS adoption of innovative IPC products: A qualitative study of SMEs in the Liverpool city region - Rocío Villacorta Linaza; Janet Hemingway; Adam P. Roberts; Becky Jones-Philips; Miriam Taegtmeyer; Richard L. Wright; Daire Cantillon; Maria Moore; Russell Dacombe; Ezekiel Boro; Aaron Argomandkhah; Carolina Velasco; et al. (PLoS ONE, 2025)
Healthcare-associated infections (HAIs) result in prolonged hospital stays and an increased incidence of infections caused by antimicrobial-resistant bacteria. Small and Medium Enterprises (SMEs) play a crucial role in developing innovative Infection Prevention and Control (IPC) solutions, but they face substantial challenges in navigating the complex NHS procurement system. This study, carried out in the Liverpool City Region in 2022, investigated these barriers. The methodology involved qualitative data collection through an online survey and five semi-structured interviews with SMEs involved in IPC innovation. The survey targeted 114 SMEs, and the interviews were conducted remotely with management teams. Data were analysed thematically using NVivo software, allowing for the identification of key barriers and recurring themes across the dataset. Key challenges identified included high market-entry costs, navigating complex regulatory and procurement frameworks, and limited access to key NHS stakeholders. These issues were compounded by fragmented decision-making processes within NHS Trusts, making it difficult for SMEs to secure product adoption. Despite these barriers, SMEs remain committed to innovating IPC solutions, driven by the potential to improve patient care and address antimicrobial resistance. This report recommends streamlining support mechanisms for SMEs, improving access to NHS decision-makers, and advocating for policy reforms to simplify the procurement process. By facilitating collaboration between SMEs, the NHS, and other stakeholders, the adoption of innovative IPC products can be accelerated, ultimately benefiting patients and addressing the significant public health threats posed by HAIs and antimicrobial resistance.